SAUR17 and SAUR50 Differentially Regulate PP2C-D1 during Apical Hook Development and Cotyledon Opening in Arabidopsis. Issue 12 (22nd October 2020) - Wang, Jiajun; Sun, Ning; Zhang, Fangfang; Yu, Renbo; Chen, Haodong; Deng, Xing Wang; Wei, Ning
Abstract : SAUR17 is highly expressed in apical hooks and cotyledons in the dark, where it promotes etiolation by protecting the phosphatase activity of PP2C-D1 against cell expansion–inducing SAURs such as SAUR50. Abstract: Following germination in the dark, Arabidopsis ( Arabidopsis thaliana ) seedlings undergo etiolation and develop apical hooks, closed cotyledons, and rapidly elongating hypocotyls. Upon light perception, the seedlings de-etiolate, which includes the opening of apical hooks and cotyledons. Here, we identify Arabidopsis Small Auxin Up RNA17 ( SAUR17 ) as a downstream effector of etiolation, which serves to bring about apical hook formation and closed cotyledons. SAUR17 is highly expressed in apical hooks and cotyledons and is repressed by light. The apical organs also express a group of light-inducing SAURs, as represented by SAUR50, which promote hook and cotyledon opening. The development of etiolated or de-etiolated apical structures requires asymmetric differential cell growth. We present evidence that the opposing actions of SAUR17 and SAUR50 on apical development largely result from their antagonistic regulation of Protein Phosphatase 2C D-clade 1 (PP2C-D1), a phosphatase that suppresses cell expansion and promotes apical hook development in the dark. SAUR50 inhibits PP2C-D1, whereas SAUR17 has a higher affinity for PP2C-D1 without inhibiting its activity. PP2C-D1 predominantly associates with SAUR17 in etiolated seedlings, which shields it from inhibitory SAURs such as SAUR50. Light signals turn off SAUR17 and upregulate a subgroup of SAURs including SAUR50 at the inner side of the hook and cotyledon cells, leading to cell expansion and unfolding of the hook and cotyledons.